Methane Mitigation in the Livestock Industry - Using Integrated Approach: A Review - Aziiba, Emmanuel Asibi (Journal of Smart Agriculture and Environmental Technology, 2025)
Agriculture is a primary source of methane (CH4), which contributes to global warming. Globally, there is a significant increase in methane emissions due to the expansion of the livestock industry. Reducing methane emissions is necessary to avert a climatic catastrophe. This article compiled and reviewed 136 published articles and online database information on greenhouse gas management from 2017 to 2024. The objective was to ascertain which technology reduces methane to the bare minimum to mitigate climate change. Mitigation systems assessed included manure acidification, animal housing systems, manure storage systems, temperature, filtration, vermicomposting, composting, biochar addition, feed additives, feeding technology, digester technology, and breed selection. It turned out that no single abatement technology can eliminate methane. Methane emissions will continue to increase if one-factor abatement is the main focus. An integrated strategy that incorporates economic and environmental assessment of livestock trade-offs, nutrition, feed quality, source, type, and breed, and feed conversion efficiency can significantly reduce methane emissions. Simulating the Earth’s carrying capacity and human demand for livestock products can reduce methane.